TINJAUAN YURIDIS TENTANG PROSEDUR PELAKSANAAN ASURANSI JIWA DALAM KECELAKAAN PENUMPANG DAN LALU LINTAS PADA PT. JASA RAHARJA( PERSERO) CABANG MELAK KUTAI BARAT - Iban Nyurang (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
abstract         In essence, every human activity in this world no matter how simple it always contains a variety of possibilities, both positir or negative. Sometimes lucky and sometimes experience losses. So it can be said, that every human activity that always contains a state of uncertainty. Things are not sure it is as a state, full of question marks, the chances of suffering a loss that will lead to a role that is not safe. Uncertain circumstances which give rise to a sense of insecurity against any possibility of suffering from the so-called risk or in other words a risk is an event that creates uncertainty, causing losses of insecurity.